SolarKAT: a solar imaging pipeline for MeerKAT - Samboco, Victória da Graça Gilberto (Rhodes University, Faculty of Science, Department of Physics and Electronics)
Solar interference poses a significant challenge in radio interferometric observations, particularly with the increasing sensitivity of modern new-generation telescopes. This thesis presents the SolarKAT pipeline, a novel approach designed to mitigate solar interference in MeerKAT observations. The pipeline incorporates a series of steps, including self-calibration (second generation calibration or 2GC), precise determination of the Sun's position, phase centre adjustments, creation of region-based masks, deconvolution, prediction, solar model subtraction, and peeling. We applied the SolarKAT pipeline to three datasets that feature the Sun in different conditions (frequency band and angular distance from the Sun to the telescope pointing position). These observations were obtained from three MeerKAT telescope surveys: ThunderKAT, MIGHTEE and LADUMA. We compared the visual images, peak fluxes, flux density, RMS and pixel distribution to evaluate the pipeline. Our results showed a notable reduction in solar interference. This is evidenced by the improved image quality, reduction in RMS and pixel distribution values, and consistent peak flux measurements after applying the pipeline. SolarKAT has not only improved the data quality but also demonstrated to be a valuable tool in producing high-quality solar images, which can be a helpful resource for solar physics and space weather forecasts. This study showcases the potential of the SolarKAT pipeline in enabling high-quality radio interferometric observations, even in the presence of solar interference. Unlike conventional methods that often discard corrupted visibilities (e.g. flagging), our approach focuses on recovering them. Additionally, the SolarKAT pipeline naturally delivers detailed images of the Sun. Our findings contribute to advancing the field of radio interferometry, providing a valuable tool for researchers seeking to enhance the accuracy of their observations and conduct studies in solar physics and space weather.
Keywords: MeerKAT; Radio interferometers; Solar activity; Radio -- Interference; Data processing